Microcredit and economic development: entrepreneurship or self-employment? - Robalo, Joana Vieira dos Reis (2015)
The present thesis aims to answer the central research question “Can microcredit be considered as an entrepreneurial activity capable of creating innovative and value-added businesses rather than a self-employment movement with few effects on economic development?”. Considering the quantitative method, three hypothesis have been tested: H1) The majority of microcredit applicants are unemployed individuals; H2) Microcredit applicants tend to apply the money in businesses with innovative features and H3) Micro entrepreneurs create only their own job and not for others. Regarding the qualitative approach, two sub questions have been placed: SQ1) In what conditions and why do people apply to microcredit programs and SQ2) In what sectors do the microcredit applicants invest? Although microcredit and microfinance industry is young in Europe and there is still a long path to cover, the research conducted showed that microcredit is a promising sector that is growing and evolving rapidly. If in previous years microcredit and microfinance projects were mostly strict to promote self-employment through traditional activities, nowadays this reality is changing and the type of business created is increasingly adopting value-added features. This research concludes that although microcredit does not nurture highly innovative businesses, it can in fact be considered as an entrepreneurial activity capable of creating value-added businesses that can have a role on job creation as well as in lessening of social exclusion, positively affecting economic development.